Nuclear Apartheid: The Quest for American Atomic Supremacy from World War II to the Present - Maddock, Shane J (The University of North Carolina Press, 2014)
After World War II, an atomic hierarchy emerged in the noncommunist world.Washington was at the top, followed over time by its NATO allies and then Israel, with the postcolonial world completely shut out.An Indian diplomat called the system "nuclear apartheid." Drawing on recently declassified sources from U.S.